The Influence of Product Quality, Service Quality and Location on Repurchase Decisions Through Consumer Satisfaction at Seblak Eci Jember Tea Buffet - Lilis Handayani; HP Agustin; Dedy Wijaya Kusuma (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
The aim of this research is to determine the influence of product quality, service quality and location on repurchase decisions through consumer satisfaction at the Seblak Eci Jember Tea buffet. The sampling technique was purposive sampling with a total of 75 respondents. Hypothesis testing data analysis in this study used IBM SPSS statistics 25 software. Hypothesis test results showed that product quality had a positive and significant effect on consumer satisfaction, service quality had no positive and insignificant effect on satisfaction. consumers, location has a positive and significant effect on consumer satisfaction, product quality has no positive and insignificant effect on repurchase decisions, service quality has a positive and significant effect on repurchase decisions, location has no positive and insignificant effect on repurchase decisions, consumer satisfaction has an effect positive and significant on repurchase decisions, consumer satisfaction is able to mediate product quality on repurchase decisions, consumer satisfaction is not able to mediate service quality on repurchase decisions, consumer satisfaction is able to mediate location on repurchase decisions